Legal Culture and Legal Consciousness of Consumers: The Influence on Regulation and Enforcement of Consumer Protection Laws - Fibrianti, Nurul; Santoso, Budi; Setyowati, Ro’fah; Rindyawati, Yuli (Journal of Indonesian Legal Studies, 2023)
Consumer protection, vital for those who consume goods and services without the intent of resale, relies on government intervention through regulatory frameworks. These regulations play a pivotal role in shaping consumer behavior, referred to globally as consumer legal culture, influenced by diverse societal backgrounds. The effectiveness of such regulations depends on alignment with consumer values. This article scrutinizes consumer behavior in Indonesia, Spain, and Australia, each characterized by unique cultures impacting consumer conduct and regulatory development. In Indonesia, consumer behavior diverges, displaying a tendency toward weaker self-protection. Despite cultural diversity, consumer awareness of product scrutiny is deficient. Affordability often outweighs safety and quality considerations, reflecting a broader trend. Legal awareness is low due to insufficient education on consumer rights. Weaknesses in consumer protection regulations and inconsistent enforcement contribute to perceptions of inadequate safeguards. Globally, varied social and cultural conditions shape consumer behavior, emphasizing the common challenge of fostering awareness for product safety and quality. The article underscores the need for culturally sensitive approaches in formulating and enforcing consumer protection measures to address diverse challenges. In summary, understanding consumer behavior in distinct cultural contexts is crucial for effective consumer protection, necessitating tailored regulatory strategies to ensure product safety and quality on a global scale.